EL RESALA.ARABIC a Won Gold Medal at the K-NOVASI 2019 - Rosjuliana Hidayu, Rosli (2019)
25th January 2019 - Rosjuliana Hidayu binti Rosli, Arabic language teacher has won a Gold medal in K-NOVASI 2019 for e-Learning Category. The competition was organised by Teaching Center & Learning Technology Universiti Kebangsaan Malaysia on 22nd until 24th January 2019. There were 400 participations from all over Malaysia. The program aims to intensify efforts to transform the learning system by promoting innovation culture in teaching and learning among academics.